Síntese e emprego do [Pd(dmba)(NCO)(PPh3)] em processos catalíticos envolvendo a preparação de derivados da uréia e de alcoxicarbonil complexos - de Lucca Neto, V. A. [UNESP]; Mauro, A. E. [UNESP]; Ananias, S. R. [UNESP]; Stevanato, A. [UNESP]; Moro, A. C. [UNESP] (Ecletica Quimica, 2006)
This work deals with the use of the cyclometallated compound [Pd(dmba)(NCO)(PPh3)] in homogeneous catalysis processes comprising the reaction of p-toluidine and p-nitrotoluene, giving N,N´-bis(4-methylphenyl)urea. The reaction was performed at 140 ºC, under 60 bar of CO pressure. On the other hand, alcoxicarbonyl compounds of the type [Pd(NCO)(CO2R)(PPh3)2] (R = Me or Et) were obtained from carbonilation reactions of [Pd(dmba)(NCO)(PPh3)] in alcohol like methanol and ethanol. It was also verified that the carbonilation processes investigated in this work afforded products with good yields.
Keywords: Cyclometallated; Homogeneous catalysis; Reductive carbonilation